PENGEMBANGAN BUKU TEKS BAHASA INDONESIA UNTUK PENUTUR ASING TINGKAT PEMULA BERBASIS KEARIFAN LOKAL WISATA MALANG - Budiana, Nia; Dewi, Putri Kumala; Hardinata, Vanda (Kantor Bahasa Banten, 2019)
The needs of BIPA learners learn about Indonesian language and wealth, one of which is through Indonesian local wisdom. The local wisdom of tourism is an attraction for foreign learners to study in Indonesia. BIPA learning must be supported by the BIPA textbook, while the BIPA textbook from the Center for Strategic Development and Linguistic Diplomacy (PPSDK) is made in general, not specific to the background of the learning objectives. For this reason, the purpose of this research is to develop BIPA textbooks based on local wisdom of tourism, especially Malang City on the aspects of systematic content, language, and systematic presentation. This type of research is development with a 4D model. The research subjects were beginner-level BIPA students at Universitas Brawijaya. The results showed that BIPA textbooks based on Malang's local tourism wisdom were decent disseminated because they met the feasibility of the aspects of the feasibility of content, language, and systematic presentation with a percentage of the feasibility of 63% to 94%.